Preparation and Characterization of Nanofluids - Singh, Gajendra (My University, 2012)
Nanofluids consist of nanometer- sized solid particles and fibers dispersed in liquids, have recently been demonstrated to have great potential for improving the heat transfer properties of liquids. In the development of energy-efficient heat transfer equipment, the thermal conductivity of the heat transfer fluid plays a vital role. However, traditional heat transfer fluids such as water, oil, and ethylene glycol mixtures are inherently poor heat transfer fluids. With increasing global competition industries have a strong need to develop advanced heat transfer fluids with significantly higher thermal conductivities than are presently available. The tested fluids are prepared by dispersing the Al2O3 into water at two different concentrations such as 0.5% and 1 %. Thermophysical properties of nanofluids are measured by KD2 Pro, Ubbelohde viscometer and specific gravity bottle. Experimental results show that thermal conductivity of nanofluids is higher than the base fluid and with increase in temperature it is increased from 3 % to 46 % (for 1 % particle concentration),and 1 % to 43 % (for 0.5 % particle concentration. Viscosity and density of nanofluids are decreasing with increase in temperature and but with increase in particle concentration, viscosity and density increased. The thermophysical properties which can be calculated by the experiments are quite high when it was compared with the respective theoretical models. And the values of all the models are quite same with each other.
M.Tech. (Chemical Engineering)
Keywords: Characterization; Nanofluids